Novel multiwalled carbon nanotube (MWCNT) modified metal oxide semiconductor field effect transistor (MOSFET) based electrode for electrophysiological measurements on human skin. Issue 5 (3rd September 2019) - Istanbullu, Mustafa; Avci, Mutlu
Abstract: Standard electrodes for electrophysiological signal acquisition in clinical applications such as electrocardiography or electromyography require the use of electrolytic gel and skin abrasion for better electrical interface between electrode and skin. Since gel dries out over a period of time, signal deterioration takes place on long duration with wet electrodes. Dry electrodes are promising alternative for long duration recording; nevertheless, they suffer from high contact impedance and motion artifacts. The proposed work introduces a novel multi-walled carbon nanotube (MWCNT) modified metal oxide semiconductor field effect transistor (MOSFET) based electrode for electrophysiological measurements on human skin. Vertically aligned metallic MWCNTs grown on the gate of MOSFETs form the contact surface of the electrode. MWCNTs penetrate the outer layer of skin for stable and improved electrical contact without the gel. The proposed electrode utilizes advantages of the MOSFET such as direct charge–current conversion, insulation between skin and instrumentation unit, and low noise pre-amplification of electrophysiological signals. Electrical equivalent of MWCNTs, design, and microfabrication of convenient MOSFET are reported. MOSFET parameters are obtained from technology computer-aided design simulation environment and combined with MWCNT parameters in the simulation program for integrated circuits emphasis. Simulated results of the proposed electrode exhibited lower contact impedance and high quality signal capture with respect to wet electrodes. The results show that the proposed electrode can be used for long duration recording of biopotentials with very high stable performance.